RECENT STRATEGIES FOR EFFICIENT SYNTHESIS AND BIOLOGICAL ACTIVITIES OF COUMARIN-CHALCONE DERIVATIVES - KONIDALA, SATHISH KUMAR; JITHENDRA CHIMAKURTHY; KOTRA, VIJAY (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Coumarins and chalcones are potential pharmacological and biologically active molecules obtained from natural source. Coumarins have predominant pharmacological activities such as antidiabetic, antitumor, and anti-inflammatory activity. Chalcones are also one of the naturally occurring pharmacologically vital molecules with different activities such as anti-inflammatory, antitumor, antimicrobial, and antimalarial activity. Literature reveals that a huge number of coumarinyl chalcone derivatives have various pharmacological activities. Coumarinyl chalcone derivatives gained more prominence due to their significant biological activities. This work explains the current information about synthesis techniques, pharmacological importance, and clinical applications of coumarinyl chalcone derivatives.